Pengembangan Media Pembelajaran Interaktif Mengunakan Ispring Suite pada materi Software Kelas VIII SMP - Julius Kalangi; Dewi Rosita (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This study uses the Research and Development (R&D) research type with the PPE model consisting of three stages, namely Planning, Production and Evaluation. The research subjects involved 35 students from class VIII (8) at SMP Samarinda as well as 3 media experts and 1 material expert. The object of the study was the Ispring Suite teaching material on Software material.The results of the study showed that the development of Ispring Suite which was tested by 3 expert media validators received a Calculation value of 172 which indicated the category of "very suitable" for use. Testing by 1 material expert obtained a calculated value of 60 which indicates the category of "very feasible" to use. The assessment of the entire Validator obtained a value of 182. Thus, the development of Ispring Suite on the material of Class VIII Software in Samarinda which was developed with the PPE model was declared very feasible based on the feasibility test of media and material experts.